2003
DOI: 10.1111/j.1748-1090.2003.tb02072.x
|View full text |Cite
|
Sign up to set email alerts
|

Welfare, husbandry and veterinary care of wild animals in captivity: changes in attitudes, progress in knowledge and techniques

Abstract: Since the first zoos were founded, attitudes to keeping wild animals in captivity have changed considerably. A much firmer conviction that animals have the capacity for consciousness and thus suffering, has been one factor in the growth in concern for welfare in recent decades. The pursuit of conservation goals and higher welfare standards has driven remarkable advances in the husbandry, veterinary science and care of wild animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Greenwood et al [ 16 ] found that ZIs “ may not be fully cognisant of the special needs of all species ”. This is not surprising, since there is a lack of biological and field data for many species held in zoos [ 24 , 25 , 26 ]. This makes it difficult to assess their basic welfare standards, let alone special needs.…”
Section: Discussionmentioning
confidence: 99%
“…Greenwood et al [ 16 ] found that ZIs “ may not be fully cognisant of the special needs of all species ”. This is not surprising, since there is a lack of biological and field data for many species held in zoos [ 24 , 25 , 26 ]. This makes it difficult to assess their basic welfare standards, let alone special needs.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, behavior alone does not always give us a comprehensive insight into an animal’s welfare state—for example, an animal may be behaving normally but may be physically unhealthy and thus its welfare may be compromised, but despite this potential limitation, an animal’s behavior often gives us important information about how that animal feels. Whilst traditionally zoos have focused on prioritizing the health of their animals, there is a recognition that health is not synonymous with welfare and that what matters to the animal is how it feels [ 48 ].…”
Section: Zoo Animal Welfarementioning
confidence: 99%
“…Among these known difficulties, the requirements for physical health and behavioural anomalies (e.g. stereotypy) have received much attention (Kirkwood 2003). However, even if captive animals are healthy and show no behavioural anomalies, they may adapt genetically to their captive environment (for a review on adaptation in captive breeding programmes see Williams and Hoffman 2009).…”
Section: Introductionmentioning
confidence: 99%